2016
DOI: 10.1002/dmrr.2818
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between SGLT2 inhibitors and DPP4 inhibitors added to insulin therapy in type 2 diabetes: a systematic review with indirect comparison meta‐analysis

Abstract: Background Both sodium glucose cotransporter 2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP4) inhibitors can be used to treat patients with type 2 diabetes mellitus (T2DM) that is inadequately controlled with insulin therapy, and yet there has been no direct comparison of these two inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 35 publications
2
40
0
8
Order By: Relevance
“…This effect size was replicated when agents were compared to DPP‐4 inhibitors as add on therapy to metformin and in triple therapy . A systematic review also demonstrates that weight reduction was achieved when SGLT2 inhibitors (2 studies with dapagliflozin and empagliflozin and 2 study with canagliflozin) were added on to insulin therapy (weighted mean difference when compared to DPP‐4 inhibitors; −2.38 kg; 95% CI −3.18 to −1.58 kg) . The weight loss with dapagliflozin is also sustained at 4 years (weight change compared with glipizide at 208 weeks; −4.38 kg; 95% CI −5.31 to −3.46 kg) .…”
Section: Effects On Glucose Controlmentioning
confidence: 85%
See 2 more Smart Citations
“…This effect size was replicated when agents were compared to DPP‐4 inhibitors as add on therapy to metformin and in triple therapy . A systematic review also demonstrates that weight reduction was achieved when SGLT2 inhibitors (2 studies with dapagliflozin and empagliflozin and 2 study with canagliflozin) were added on to insulin therapy (weighted mean difference when compared to DPP‐4 inhibitors; −2.38 kg; 95% CI −3.18 to −1.58 kg) . The weight loss with dapagliflozin is also sustained at 4 years (weight change compared with glipizide at 208 weeks; −4.38 kg; 95% CI −5.31 to −3.46 kg) .…”
Section: Effects On Glucose Controlmentioning
confidence: 85%
“…Indirect comparison meta‐analyses of efficacy in RCTs have also been performed. A comparison of 14 RCTs of SGLT2 inhibitors versus placebo (5 studies) and DPP‐4 inhibitors versus placebo (9 studies) as add on therapy to insulin demonstrated greater HbA1c reduction with SGLT2 inhibitors (relative HbA1c reduction; −0.24%; 95% CI −0.43 to −0.05%) . Neither class increased hypoglycaemia risk .…”
Section: Effects On Glucose Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Esposito et al reported a tendency of a slight increase in body weight with the use of DPP-4 inhibitors [25], and the extent of the weight gain was similar to that observed in this study. Metaanalyses have reported that DPP-4 inhibitors, even when used as an add-on to insulin, are almost weight neutral [26][27][28]. In patients receiving insulin, weight gain was likely to occur [5].…”
Section: Weight Gainmentioning
confidence: 99%
“…In a meta‐analysis of second‐line treatments, DAPA provided similar HbA1c control with similar or lower risks of hypoglycaemia compared with DPP‐4 inhibitors, TZDs and SUs over 1 year, and provided the added benefit of weight loss . In a second meta‐analysis, SGLT2 inhibitors provided better glycaemic control and greater weight loss compared with DPP‐4 inhibitors without an increase in hypoglycaemia . This study was conducted to compare healthcare resource utilization and costs over 1 year among patients who initiated DAPA compared with patients who initiated SITA in a real‐world clinical setting.…”
Section: Introductionmentioning
confidence: 99%